2011
DOI: 10.1016/j.visres.2011.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Magnocellular and parvocellular influences on reflexive attention

Abstract: Previous studies have provided conflicting evidence regarding whether the magnocellular (M) or parvocellular (P) visual pathway is primarily responsible for triggering involuntary orienting. Here, we used event-related potentials (ERPs) to provide new evidence that both the M and P pathways can trigger attentional capture and bias visual processing at multiple levels. Specifically, cued-location targets elicited enhanced activity, relative to uncued-location targets, at both early sensory processing levels (in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Thus, P3 amplitudes, being larger after left than right T2 as observed in a previous two-stream RSVP study (Verleger et al, 2011), might be related to greater perceptual distinctiveness of left T2 as a consequence of attention being biased to the left hemifield. Importantly, in the context of cueing paradigms, salient task-irrelevant cues that reflexively attract attention were shown to increase P3 amplitude evoked by targets presented in validly cued locations at short cuestimulus intervals (Ries & Hopfinger, 2011;Hopfinger & Mangun, 1998. This increase in P3 amplitude was interpreted to reflect that stimuli at cued locations are treated as more important in processing at further stages than stimuli at uncued locations (Hopfinger & Mangun, 1998).…”
Section: Introductionmentioning
confidence: 96%
“…Thus, P3 amplitudes, being larger after left than right T2 as observed in a previous two-stream RSVP study (Verleger et al, 2011), might be related to greater perceptual distinctiveness of left T2 as a consequence of attention being biased to the left hemifield. Importantly, in the context of cueing paradigms, salient task-irrelevant cues that reflexively attract attention were shown to increase P3 amplitude evoked by targets presented in validly cued locations at short cuestimulus intervals (Ries & Hopfinger, 2011;Hopfinger & Mangun, 1998. This increase in P3 amplitude was interpreted to reflect that stimuli at cued locations are treated as more important in processing at further stages than stimuli at uncued locations (Hopfinger & Mangun, 1998).…”
Section: Introductionmentioning
confidence: 96%
“…Previous fi ndings indicate that the viewing space is divided into four quadrants: upper left, lower left, lower right, and upper right (e.g., Niebauer & Christman, 1998 ;Nicholls, et al ., 2004 ;Thomas & Elias, 2010, 2011, 2012. Considering the data, within the upper or lower visual fi elds, diff erences in upper and lower stimulus manipulations altered the magnitude of the bias, but did not change the bias direction relating to the upper or lower fi eld presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we suggest that the VEP effect contralateral to the target position is probably related to a reduced salience of the target stimulus. Correspondingly, the involuntary orientation response to the target stimulus, which indicates a biasing of visual processing (Hopfinger & Ries, ; Ries & Hopfinger, ), is attenuated by moderate alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%
“…In VEP studies, the shift of attention to the attended stimulus leads to an amplitude enhancement at contralateral electrode leads. Numerous studies have shown that the attentional modulation of sensory processing depends on top-down control settings, such as task instruction (Heinze, Luck, Mangun, & Hillyard, 1990;Lange, Wijers, Mulder, & Mulder, 1999), but also on reflective bottom-up mechanisms, such as stimulus salience (Hopfinger & Ries, 2005;Ries & Hopfinger, 2011).…”
mentioning
confidence: 99%